The Effect of Social Support on Work-Life Balance-Mediated Subjective Well-Being and the Role of Self-Efficacy as a Moderating Variable - Andra Alif Wastito; Survival; Wahju Wulandari (Journal of Management Research and Studies, 2025)
The purpose of this study was to determine the effect of social support on subjective well-being mediated by work-life balance and the role of self-efficacy as a moderating variable. This study uses a quantitative research design and the type of research used is to explain the causal relationship between research variables through testing previously formulated hypotheses. The population in this study were all employees of PT. Widatra Bhakti, totaling 300 employees. The determination of the number of samples in this study used the Slovin formula, which amounted to 75 respondents. The sampling technique used was probability sampling with the technique taken, namely simple random sampling. The research design used to analyze and interpret the data was inferential statistical analysis, namely SEM-PLS using SmartPLS 4. The results showed that there was no significant effect between social support and subjective well-being. There was a significant effect between social support and work-life balance. There was a significant effect between work-life balance and subjective well-being. There was no significant effect between self-efficacy and subjective well-being. There was a significant effect between social support and subjective well-being which was fully mediated by work-life balance. There was a significant effect between social support and subjective well-being which was purely moderated by self-efficacy.